Computational systematic selectivity of the Fasalog inhibitors between ROCK-I and ROCK-II kinase isoforms in Alzheimer's disease. (August 2020) - Song, Laijun; Zhu, Chunyu; Zheng, Wenxin; Lu, Dan; Jiao, Hong; Zhao, Rongbing; Bao, Zhonglei
Graphical abstract: Highlights: The Fasalog selectivity between ROCK-I and ROCK-II kinase isoforms is investigated systematically. The 1, 4-diazepane moiety plays an important role in Fasalog selectivity. The region out of kinase active site can indirectly influence Fasalog selectivity through allosteric effect. Several isoform-selective Fasalogs are identified. Abstract: Human Rho-associated coiled-coil forming kinase (ROCK) is a class of essential neurokinases that consists of two structurally conserved isoforms ROCK-I and ROCK-II; they have been revealed to play distinct roles in the pathogenesis of Alzheimer's disease (AD) and other neurological disorders. Selective targeting of the two kinase isoforms with small-molecule inhibitors is a great challenge due to the surprisingly high homology in kinase domain (92 %) and the full identity in kinase active site (100 %). Here, we describe a computational protocol to systematically profile the selectivity of Fasudil and its 25 analogs (termed as Fasalogs) between the two kinase isoforms. It is suggested that the substitution of Fasudil's 1, 4-diazepane moiety with rigid ring such as Ripasudil and Dimehtylfasudil would render the resulting inhibitors of ROCK-II over ROCK-I ( II -o- I ) selectivity, while the substitution with long, flexible group such as H-89 and BDBM92607 tends to have I-o-II selectivity. Structural analysis reveals that the inhibitor affinity is not only determined by the identical active site, but also contributed from the non-identical first and second shells of the site as well as other non-conserved kinase regions, which can indirectly influence the active site and inhibitor binding through allosteric effect. A further kinase assay basically confirms the computational findings, which also exhibits a good consistence with theoretical selectivity over 10 tested samples ( R p  = 0.89). In particular, the Fasalog compounds Dimehtylfasudil and H-89 are identified as II -o- I and I -o- II selective inhibitors. They can be considered as promising lead molecular entities to develop new specific ROCK isoform-selective Fasalog inhibitors.